Comercialização de flores e folhagens de corte em Pernmabuco : práticas, possibilidades, perspectivas (uma análise em período pandêmico: 2020/2021) - FERREIRA, Isabel Verônica Sarinho (2022)
Floriculture is one of the most promising sectors of Brazilian agribusiness as a competitive, dynamic and profitable activity. However, it still lacks research to promote the activity at the local level and that contribute to the construction of poles of regions. Seeking to establish this problem, the objective of this research is how the commercialization process is analyzed and developed, specifically the market for cut flowers and foliage in productive areas in the state of Pernambuco. The research is descriptive and qualitative in nature, using the case study as a research method. As a data collection instrument, a semi-directive interview was carried out with two companies in the plant market, namely: the company AsFlores, located in the municipality of Gravatá, consolidated specialized in the cultivation of natives of temperate climate, and in Mumbecas, zona da mata, in Paulista, dedicated to the cultivation of tropical plants, in addition to these, with a manager from CEASA/PE. As a method of data collection, a documental survey was carried out, in addition to direct observation, which was also studied during the interviews. For the scope analysis, the methodology of 'content analysis' was used, in which the focus of data or message that the interviewee wanted to reveal, more than what he actually said was. Realizing the need to carry out the cultivation together in the direction as management practices for the sale of products, each producer launched itself individually in survival strategies according to the specificities of its members, and CEAS in terms of cultivation/PE played an activated posture to intensify as sales during the pandemic period. Note the cultivation of flowers (both temperate and tropical) an activity with great possibilities to reinvent itself, of expressive value to the well-being of the human being. The market showed itself due to a diversified niche of use of broad cut plants. However, it still needs to improve care on offer and focus on regional demands, be it post-harvest care, relationships along the chain and the market.